Water treatment made simple : for operators. - Sarai, Darshan Singh, ....- (Hoboken : Wiley, 2006)
This is a concise guide to the ins and outs of water treatment plants. "Water Treatment Made Simple" is an easy-to-understand introduction to the increasingly complex functions of water treatment plants. It's a perfect primer for anyone pursuing Water Treatment Plant Operator certification, and a succinct refresher for new hires since it covers all the fundamental proficiencies of water treatment, including laboratory testing, hydraulics, mathematics, chemistry, water transmission, disinfection, and microbiology. "Water Treatment Made Simple" also serves as a highly illustrative reference featuring dozens of handy problem-solving tables that are invaluable for troubleshooting on site, and brief and simplified versions of fundamental principles in each chapter, supplemented with common problems and possible solutions. It features: unique problem-solving tools to help operators diagnose and remedy problems throughout the treatment process; self-review questions that help readers qualify their understanding of covered topics; a comprehensive list of references for further study; and a helpful glossary and appendixes for quick reference
Keywords: Afvalwaterzuivering; Drinkwaterzuivering